Strengthening Digital Literacy through Public Innovation: The Socio-political Value of Pustaka Ambaralaya in Bali - Destri, Modesta; Lukman, Juwita Pratiwi (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
The advancement of information technology has driven the transformation of library services into digital systems, enhancing public access to information and literacy. This study analyzes the implementation of the Pustaka Ambaralaya application by the Bali Provincial Regional Library as an innovation in digital public services. Employing a qualitative descriptive approach, data were collected through interviews with administrators and users, as well as direct observation. The analysis draws on Everett Rogers’ diffusion of innovation theory, focusing on five characteristics: relative advantage, compatibility, complexity, trialability, and observability. Findings show that Pustaka Ambaralaya offers unrestricted access to information, aligns with the digital habits of Balinese society, and features a simple, user-friendly interface. Despite lacking a trial version, its free access lowers barriers and enhances trialability. Observational data reveal a significant increase in user engagement with digital library services. The study concludes that Pustaka Ambaralaya serves as an effective public innovation for fostering digital literacy and reading culture. The novelty lies in its emphasis on the socio-political value of digital innovation in strengthening human capital at the regional level, offering significant contributions to social and political science discourse, particularly in the area of technology-based public service innovation.